Persepsi Cita Rasa Kopi Siap Saji dan Perbedaan Warna Kemasan - Kharismahayati, Pristi; Sugiyanto (ANIMA Indonesian Psychological Journal, 2006)
This research investigated the effect of package color on flavor perception. The hypothesis of this research was that package colors would affect flavor perception, and that blue-colored package would result in more positive flavor perception than red. These two chromatic colors were chosen as the package colors, as well as the achromatic white color. The samples (N = 48) were undergraduate students of the Faculty of Psychology, Gadjah Mada University, who volunteered as subjects. They were assigned to evaluate the flavor of coffee served in the three different-color packages A flavor perception scale was employed to collect the data through a counter-balance experimental design method. Results revealed that blue-colored package elicited more positive response than red, produc- ing more positive flavor perception. The same result was obtained from the white-colored package. Results also showed that red-colored package was ineffective in producing positive flavor perception.Penelitian ini meneliti akibat warna kemasan terhadap persepsi cita rasa. Hipotesis peneli- tian ini adalah bahwa warna kemasan memengaruhi persepsi cita rasa, dan warna biru menghasilkan persepsi cita rasa yang lebih positif daripada warna merah. Dua warna khromatik tersebut dipilih sebagai warna kemasan. Selain itu, juga dipakai warna akhromatik(putih). Sampel (N = 48) adalah relawan mahasiswa Fakultas Psikologi UGM, yang diminta menilai cita rasa kopi yang dikemas dalam 3 jenis warna tersebut. Data diperoleh melalui pengisian skala persepsi cita-rasa yang telah disiapkan dengan metode eksperimen dengan desain counterbalance. Hasil mengesankan bahwa kemasan berwarna biru lebih menarik daripada yang merah, sehingga menimbulkan persepsi cita rasa yang lebih positif. Demikian juga dengan warna putih. Hasil juga menunjukkan bahwa kemasan dengan warna merah kurang efektif dalam menimbulkan persepsi cita rasa yang positif.